The Effect of Retrieval Focus and Emotional Valence on the Medial Temporal Lobe Activity during Autobiographical Recollection - Denkova, Ekaterina; Dolcos, Sanda; Dolcos, Florin (Frontiers in Behavioral Neuroscience, 2013)
Laboratory-based episodic memory studies, using micro-events (pictures/words), point a role of the amygdala (AMY), an emotion-based region, in the encoding and retrieval of emotionally-valenced memories. However, autobiographical memory (AM) studies, using real-life personal events, do not conclusively support AMY’s involvement in AM recollection. This could be due to differences in instructions across the AM studies – i.e., whether emotional aspects were explicitly emphasized or not. The present study investigated the effect of retrieval focus on activity in emotion (AMY) and memory (hippocampus - HC) based regions of the medial temporal lobe in seventeen subjects, who remembered emotional AMs while event-related fMRI data were recorded. The retrieval focus was manipulated by instructions to focus either on emotional (Emotion condition) or on other contextual (Context condition) details of the recollected AMs. The effect of retrieval focus according to the valence of AMs was also investigated by involving equal proportions of positive and negative AMs. There were four main findings, showing both similarities and differences in retrieving positive and negative AMs. Regarding similarities, (1) focusing on Emotion was associated with increased scores of subjective re-experience of emotion and increased activity in the left AMY, for both positive and negative AMs, compared to focusing on Context; (2) the subjective emotional ratings were also positively correlated with bilateral AMY activity for both positive and negative AMs. Regarding differences, (3) focusing on Emotion was associated with increased activity for positive but not for negative AMs in the right AMY, and with (4) opposing patterns of activity linked to the valence of AMs in the left HC - i.e., increased activity for positive and decreased activity for negative AMs. These findings shed light on the role of AMY and HC in emotional AM recollection, linked to the retrieval focus and the valence of memories.